Optimalisasi Struktur Modal Dengan Trade Off Theory Pada Bank Umum Syariah - Budi Gautama Siregar; Muhammad Salman; Aswadi Lubis (Program Studi Akuntansi Fakultas Ekonomi Universitas Samudra, 2024)
This study aims to evaluate PT's financial performance. Bank Mega Syariah through liquidity ratio analysis with the Financing to Deposit Ratio (FDR), Capital Adequacy Ratio (CAR), Return on Assets (ROA), and Return on Equity (ROE) approaches. This research is descriptive quantitative, where the data is analyzed, and the results are described to provide an overview of the bank's financial performance. The data used is secondary data from PT's financial statements. Bank Mega Syariah for the period 2013-2021. The results show that the financing-to-deposit ratio (FDR) has fluctuated, with the highest levels in the second and third quarters of 2015, at 104.19% and 102.89%, respectively. Based on the analysis of the Capital Adequacy Ratio (CAR), PT. Bank Mega Syariah shows excellent capital. The ROA study shows several periods that are considered unhealthy based on Bank Indonesia standards, namely in the third and fourth quarters of 2016, 2017, and the fourth quarter of 2021. ROA describes the ability of PT. Bank Mega Syariah is making profits from its assets. Meanwhile, the ROE analysis shows that the condition of PT. Bank Mega Syariah is included in the unhealthy category. This research only focuses on the study of liquidity, solvency, and profitability ratios, so there is still an opportunity for further research that can explore other aspects, such as profitability, growth, or the application of a balanced scorecard.